Combined Effect of Drought Stress and Elevated Atmospheric CO2 Concentration on the Yield Parameters and Water Use Properties of Winter Wheat (Triticum aestivum L.) Genotypes. (19th May 2016) - Varga, B.; Vida, G.; Varga‐László, E.; Hoffmann, B.; Veisz, O.
Abstract: The decline in the amount of water available to plants will lend growing importance to the dynamics of water uptake and to water use efficiency (WUE; g kg −1 ) in cereals. Water use properties were investigated in terms of the phenological and yield parameters of five winter wheat genotypes in a greenhouse experiment carried out in climate‐controlled chambers. The plants were grown either with optimum water supplies or with simulated drought in two phenophases, combined with different CO2 concentrations (ambient and enriched to 700 and 1000 ppm). Multivariate analysis showed that the CO2 concentration alone significantly influenced water use and water use efficiency but in combination with the cultivars, it also had a significant influence on the grain yield and in a combination with the water supply on the straw biomass, respectively. Higher CO2 concentration significantly reduced the water uptake and improved the WUE values in both the drought treatments. All three factors investigated were found to have a significant influence on the water consumption during the growing season, and the interaction between CO2 and the cultivar influenced WUE. The least change in WUE was detected for Bánkúti 1201 (1.35–1.86 g kg −1 ), while Mv Mambó, Plainsman V and Mv Toborzó formed a group responding similarly to various environmental effects (1.85–2.55 g kg −1 ; 1.57–2.34 g kg −1 and 1.45–2.24 g kg −1, respectively).